The role of similarity and complementarity in the selection of potential partners for open innovation projects in family firms - Julia K. de Groote; Sabrina Schell; Nadine Kammerlander; Andreas Hack (Small Business Economics, 2022)
Despite the increasing importance of open innovation endeavors, the process by which firms select partners for open innovation is not well understood. Even less is known about how family firms, which are characterized by their resource scarcity and desire for control, handle these processes. We aim to address this gap in the literature by investigating this selection process using a qualitative approach. Our findings are based on data gathered in 53 interviews from ten case studies and expert interviews, as well as secondary data. We find that, in order to engage in collaboration, family firms must manage their perceptions of the similarities and complementarities between themselves and their potential partner and integrate these into an accepted level of anticipated fit. During the selection phase, the elements of fit are weighed in light of the openness of the given firm and preferred levels and mechanisms of control, which are influenced by the family in the family firm. If the fit is deemed sufficient to enter into a partnership, the partnership is then advanced to the collaboration phase, where anticipated fit is translated into experienced fit, and aspects of similarity and complementarity are reassessed; this may potentially end existing partnerships, feeding back to future evaluations of fit and accordingly influencing future partnerships.
Keywords: M14; D8; L14; L21; 330; Open innovation; Family firms; Partner selection; Fit; Complementarity; Similarity